Pengaruh Media Kartu Punggung terhadap Pemahaman Konsep Matematika Siswa Kelas II SD Inpres Kuanino 2 - Lumban Gaol, Sulastry Damayanti; Ati, Chintia M.P.; Hendrik, Hingrida Margarita Anastasia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics conceptual understanding is an essential competency that needs to be developed from the elementary school level. However, the abstract nature of mathematical concepts can make it difficult for students to connect mathematical representations with meaningful understanding. This study aimed to examine the effect of using Kartu Punggung as an instructional medium on the mathematical conceptual understanding of second-grade elementary school students. This study employed a quantitative approach with a one-group pretest–posttest design. The participants were 20 second-grade students of SD Inpres Kuanino 2, selected through saturated sampling. Data were collected using a mathematical conceptual understanding test and an observation sheet of students’ learning activities. Data analysis involved the Shapiro–Wilk normality test and the Wilcoxon Signed-Rank Test because the data were not normally distributed. The results showed an increase in the students’ mean score from 61.0 on the pretest to 84.0 on the posttest, representing an increase of 23 points. The Wilcoxon Signed-Rank Test revealed a statistically significant difference between the pretest and posttest scores (Asymp. Sig. (2-tailed) < 0.001), with all 20 students showing improved scores after the intervention. Observation results also indicated good to very good student engagement, particularly in participation, cooperation, communication, and the activity of finding matching cards. These findings indicate that the use of Kartu Punggung has a significant positive effect on students’ mathematical conceptual understanding and can serve as an interactive and collaborative instructional medium in elementary mathematics learning